Retention of Posterior Cruciate Ligament Alone May Not Achieve Physiological Knee Joint Kinematics After Total Knee Arthroplasty: A Retrospective Study. (20th January 2021) - Moewis, Philippe; Duda, Georg N.; Trepczynski, Adam; Krahl, Leonie; Boese, Christoph K.; Hommel, Hagen
Abstract : Background: The apparently physiological kinematics of the bicruciate-stabilized total knee arthroplasty (BCS TKA) systems have been attributed to the anterior and posterior post-cam mechanism. Although comparisons between TKA designs with either a retained or a sacrificed cruciate ligament have been conducted, we are not aware of any analyses of 2 implants with identical bearing geometry but different cruciate-ligament strategies under equal loading conditions. Knowledge about the kinematic effect of the different cruciate ligament strategies would potentially be valuable to facilitate preoperative planning and decision-making with regard to selecting the most appropriate implant for a patient. Methods: This retrospective study included 20 patients: 10 treated with a BCS and 10 treated with a cruciate retaining (CR) TKA. Fluoroscopic analyses during high-flexion activities (unloaded flexion-extension and loaded lunge) were conducted at 24 months postsurgery. All patients completed the Knee Society Score, Forgotten Joint Score, and High-Flexion Knee Score questionnaires preoperatively and postoperatively. Results: The BCS cohort showed greater femoral lateral rollback as well as a medial pivot in both activities. In contrast, the CR cohort showed a significant increase in anterior translation on the medial compartment as well as almost absent femoral lateral rollback. Higher clinical scores were observed in the BCS cohort. Conclusions: At 24 months postsurgery, despite equal bearing geometry, retention of the posterior cruciate ligament in the CR cohort apparently was insufficient to reduce anterior shift. The BCS cohort showed expected knee joint kinematics; however, the kinematics in this cohort could eventually benefit from a smooth transition between the interchanging surfaces. Further investigation should be focused on the surgical technique and its interaction with the TKA design. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.